Aspects of âContextâ in the Modern Linguistic Studies - Mohammad Ismail-Bassal; Fatema Ballah (دراسات في اللغة العربيّة وآدابها)
The study of âcontextâ has obtained a significant place in contemporary linguistic studies and many linguistic scholars, both in early and modern times, spent much effort on this domain until it became a fully-fledged theory by the English scholar Firth. In the past, scholars paid attention to the âContextâ and its effect on the meaning studied the conditions surrounding the speech context .They considered the relation between the level of discourse and words. They found that pronunciation does not express the meaning if the context is disregarded. This principle was followed by a number of scholars: Aljahez, Ibn Jinni, Abdulkaher and Al-Jorjany, who established the Theory of Composition, which refers to the integration of âContextâ and ideas to constitute an integral theory. Their effort realized in the content of the Arabic cultural heritage such as explication, Koranic studies, hadith, rhetoric, syntax and morphology. In modern linguistic studies, Firth developed the Theory of âContextâ and make it a comprehensive linguistic theory that affected Arab as well as Western Linguists who followed him. This research deals with aspects of âContextâ in the work of Western linguists before and after Firth, and Arab linguists who highly admired Western linguistic studies.